Expressão, purificação e caracterização de uma catalase de Serratia marcescens - Pacheco, Alberto Enrique Maestre (2021)
Enzymes constitute a fundamental factor in a broad range of industrial process due to their high catalytic efficiency and low energy consumption. Thus, presenting a fast growth, versatility and high production levels, microorganisms become an important source of enzymes of industrial interest; such as catalases, which are characterized for by its applications in different sectors: food, textile, pharmacological, dental, among others. However, there are some limitations in the production of many enzymes through conventional process. One of them is the difficult in mimic the environmental and nutritional conditions for the growth of some microorganisms in laboratorial. So, some techniques of genetic engineering as heterologous expression in different expression systems, as Escherichia coli and Pichia pastoris, constitute an interest alternative, since they are versatile expression systems for the production of innumerable enzymes and products of biotechnological interest in large scale. This work has as main objective the establishment of a recombinant expression system of a catalase from Serratia marcescens in cells of Pichia pastoris and Escherichia coli. The Kat fragment (encoding an alkaline catalase) from bacterial strain Serratia marcescens FZSF01 was previously subcloned in the expression vectors pPICZαA and pET-28a. The recombinant plasmid pPICZαA_Kat was used to transform cells of P. pastoris KM71H and X-33, while the recombinant vector pET-28_Kat was used to transform cells of E. coli Rosetta (DE3). The recombinant clones of P. pastoris KM71H and X-33 were induced with methanol (final concentration of 0.75% and 1%, respectively) for a period of 144 hours. The induction in E. coli was made with IPTG in a final concentration of 0,4 mM at 37 ºC and the purification was made by affinity chromatography in nickel resin. The purified catalase enzyme activity was made by spectrophotometer method. Analysis of expression and purification were made in SDS-PAGE 12% colored with Comassie. Catalase expression in P. pastoris was observed in small scale, being necessary the standardization of the expression assays in a larger scale. In E. coli Rosetta (DE3) cells, it presented significative expression rates, presenting a partial solubility, which allowed the protein purification, obtaining a yield of 0.51 mg per liter of culture. After, it was done enzymatic assays that demonstrated that the catalase was active and it presented a Michaelian behavior.